Outcomes associated with trial of labor after cesarean in women with one versus two prior cesarean deliveries after a change in clinical practice guidelines in an academic hospital*. (2nd May 2020) - Davidson, Christina; Bellows, Patricia; Shah, Utsavi; Hawley, Lauren; Drexler, Kathleen; Gandhi, Manisha; Eppes, Catherine; Sangi-Haghpeykar, Haleh
Abstract: Objective: In 2010, the American College of Obstetricians & Gynecologists (ACOG) published a new clinical practice guideline on trial of labor after cesarean (TOLAC) that was considered less restrictive. It allowed for offering TOLAC to women with two prior cesarean deliveries, even without a prior vaginal delivery, and for labor induction. As a result, our hospital, a public tertiary care academic center, updated our TOLAC practice guideline to reflect ACOG's new recommendations. We thus aim to evaluate maternal and neonatal outcomes for women undergoing TOLAC with 1 versus 2 prior cesareans, with and without a prior vaginal delivery, following these clinical practice changes at our hospital. Study design: This was a secondary analysis of a 2-year retrospective cohort following implementation of a hospital guideline in women undergoing TOLAC with a live, cephalic, singleton without lethal anomaly ≥24 0/7 weeks and 1 or 2 prior cesarean deliveries. Maternal and neonatal outcomes in women with one prior cesarean were compared to women with two prior cesareans. The primary outcome was composite maternal morbidity (uterine rupture, uterine dehiscence, hysterectomy, transfusion, postpartum venous thromboembolism, delivery/surgical injury, chorioamnionitis or endometritis, shoulder dystocia, death). Secondary outcomes included neonatal morbidity. The analysis was performed in SAS; p < .05 was considered significant. Results: Seven hundred women with one prior cesarean and 73 women with two prior cesareans underwent TOLAC after the 2011 guideline implementation. Post guideline maternal demographics, labor length, comorbid conditions, simplified Bishop score, and induced labor were similar between groups. Composite maternal morbidity was similar between groups (18.3 versus 23.3%, p = .30 for women with 1 versus 2 prior cesarean deliveries, respectively). The same was true when comparing women with 1 versus 2 prior cesareans who had never had a prior vaginal delivery (25.5 versus 33.3%, p = .28 for 1 versus 2 prior cesarean deliveries, respectively). There were no differences in neonatal outcomes. Vaginal birth after cesarean (VBAC) success rates were similar between groups (78.9% in women with 1 prior cesarean versus 74.0% in women with 2 prior cesareans, p =.33), even when only analyzing women without a prior vaginal delivery (69.4% in women with 1 prior cesarean versus 71.4% in women with 2 prior cesareans, p = .78). Conclusion: Adoption of ACOG's TOLAC practice changes, specifically offering TOLAC to women with two prior cesareans even without a prior vaginal delivery, and offering induction of labor regardless of cervical favorability, may increase VBAC rates without increasing maternal or neonatal morbidity from TOLAC.